2013
DOI: 10.1038/nm.3174
|View full text |Cite
|
Sign up to set email alerts
|

Poor-prognosis colon cancer is defined by a molecularly distinct subtype and develops from serrated precursor lesions

Abstract: Colon cancer is a clinically diverse disease. This heterogeneity makes it difficult to determine which patients will benefit most from adjuvant therapy and impedes the development of new targeted agents. More insight into the biological diversity of colon cancers, especially in relation to clinical features, is therefore needed. We demonstrate, using an unsupervised classification strategy involving over 1,100 individuals with colon cancer, that three main molecularly distinct subtypes can be recognized. Two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
450
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(485 citation statements)
references
References 45 publications
16
450
0
5
Order By: Relevance
“…In this study, we observed that isoquercitrin combines two interesting aspects for anti-tumoral research. First, the flavonoid blocks the Wnt signaling, most likely at the nuclear complex, between ␤-catenin and TCF, which supports its potential to interfere with tumor growth in other cell types as most colon tumors accumulate ␤-catenin in the nucleus (27,30,31). Second, isoquercitrin shows lower toxicity than quercetin, a known Wnt inhibitor already tested in clinical trials (38 -40).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we observed that isoquercitrin combines two interesting aspects for anti-tumoral research. First, the flavonoid blocks the Wnt signaling, most likely at the nuclear complex, between ␤-catenin and TCF, which supports its potential to interfere with tumor growth in other cell types as most colon tumors accumulate ␤-catenin in the nucleus (27,30,31). Second, isoquercitrin shows lower toxicity than quercetin, a known Wnt inhibitor already tested in clinical trials (38 -40).…”
Section: Discussionmentioning
confidence: 91%
“…Most colorectal carcinomas harbor genetic alterations that result in stabilization of ␤-catenin, leading to abnormal stimulation of canonical Wnt signaling (30,31). We used HCT-116, DLD-1, and SW480 cells that have mutations in components of Wnt/␤-catenin to investigate the cell growth inhibitory effects of isoquercitrin.…”
Section: Discussionmentioning
confidence: 99%
“…Our work in human tumours shows that aberrant epithelial and/or mesenchymally derived GREM1 expression is associated with colorectal cancer subtypes that respond poorly to current chemotherapeutic regimes and have a dismal outcome 45. Given the demonstrated role of GREM1 in imposing a stem cell phenotype on cells outside the crypt base, it seems plausible that the poor treatment response may be secondary to an effect of GREM1 on cancer stem cell plasticity.…”
Section: Discussionmentioning
confidence: 86%
“…Several recent publications have sought to classify and subtype colorectal cancer based on (epi)genetic mutation and gene expression pattern 45, 46, 47. These molecular profiles correlate with variable prognosis and response to therapy and appear to reflect considerable differences in tumour subtype biology that cannot be predicted from their acquired epithelial genetic mutation burden alone.…”
Section: Genetic and Environmental Interaction And Crc Heterogeneitymentioning
confidence: 99%
“…CDX2 appears to be differentially phosphorylated along the crypt-villus axis by the mitogen-activated protein kinases (MAPK), and this modulates CDX2 transcriptional activity and half-life (10 -12). The expression of CDX2 has been found to be altered in human CRC in relation to the tumor grade (13)(14)(15), and its decrease correlates with poor prognosis (16,17). Moreover, reduction of CDX2 expression facilitates tumor progression of murine models of genetically or chemically induced CRC (18,19).…”
mentioning
confidence: 99%